An introduction to efficiency and productivity analysis (Klwer Academic Publishers, 2005)
The authors introduce the four major methods economists use to analyze efficiency and productivity: econometric estimation of average response, index numbers, data envelopment analysis (DEA), and stochastic frontier analysis. They intend the book primarily as a text for students in economics and also for students in other disciplines, such as business administration. … On the whole, I rate the book as excellent